Recent discovery of a unique Paleolithic industry from the Yumidong Cave site in the Three Gorges region of Yangtze River, southwest China. (1st April 2017) - Wei, Guangbiao; Huang, Wanbo; Boëda, Eric; Forestier, Hubert; He, Cunding; Chen, Shaokun; Zhao, Jianxin; Li, Yinghua; Hou, Yamei; Pang, Libo; Wu, Yan
Abstract: The Three Gorges of Yangtze River, southwest China, abundant in human and faunal fossils, and lithic artifacts, represents an important site complex for understanding hominin dispersion and adaptations during the Pleistocene. The Yumidong Cave is a newly-discovered Paleolithic site in this region which yielded a large number of animal fossils and lithic artifacts. U–Th dating in conjunction with biostratigraphic analysis indicated that the archaeological remains were deposited during a long sequence from ca. 400 to 8 ka (Middle Pleistocene to Holocene). Lithic technological analysis indicated an original material shaped on massive limestone blocks with chaîne opératoire consisted of selection, shaping and retouching. The volumetric structures of selected blanks are regrouped into three categories: structures with bevel(s), trihedral structure and convergent ones. The outline of cutting-edge is predonimated by denticulate ones, followed by saw-like ones, rostrum, convergent with a denticulate edge and beaked ones. Despite showing nothing in common with Europe, Africa, the Near East and even the Indian Subcontinent and northern China, the lithic assemblage of the Yumidong Cave exhibits a strong coherence and presents more similarity to mainland Southeast Asia with heavy, angular and massive stone tools made on pebble, cobble and without the Levallois, Discoid, and blade/bladelet phenomenon. The lithic assemblage of Yumidong Cave may represent material clues of a potential local technological center of origin in unique technical world of Central-South China and its uniqueness would be understandable as the result of a successful adaptation of hominids to a specific environment. Yumidong lithic material deconstructs the existing paradigm for a long period of time and presents new ideas and new facts for the technic evolution in South China.